2020
DOI: 10.1159/000508952
|View full text |Cite
|
Sign up to set email alerts
|

Using Enhanced Depth Imaging Optical Coherence Tomography-Derived Parameters to Discriminate between Eyes with and without Glaucoma: A Cross-Sectional Comparative Study

Abstract: Introduction: New technologies have been developed in order to decrease interpersonal influence and subjectivity during the glaucoma diagnosis process. Enhanced depth imaging spectral-domain OCT (EDI OCT) has turned up as a favorable tool for deep optic nerve head (ONH) structures assessment. Objective: A prospective cross-sectional study was conducted to compare the diagnostic performance of different EDI OCT-derived parameters to discriminate between eyes with and without glaucoma. Material and Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The authors reported that neural tissue-based parameters had diagnostic performances comparable to that of RNFL thickness, and neural tissue-based indices had better results compared with laminar parameters. Unlike our study, their study group consisted of a heterogeneous population, including patients with primary open angle glaucoma, primary angle-closure glaucoma, and secondary glaucoma 29. In another study, researchers investigated structural and functional correlations and found better results for neural tissue-based indexes compared with LC-derived parameters 30.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The authors reported that neural tissue-based parameters had diagnostic performances comparable to that of RNFL thickness, and neural tissue-based indices had better results compared with laminar parameters. Unlike our study, their study group consisted of a heterogeneous population, including patients with primary open angle glaucoma, primary angle-closure glaucoma, and secondary glaucoma 29. In another study, researchers investigated structural and functional correlations and found better results for neural tissue-based indexes compared with LC-derived parameters 30.…”
Section: Discussionmentioning
confidence: 86%
“…Unlike our study, their study group consisted of a heterogeneous population, including patients with primary open angle glaucoma, primary angleclosure glaucoma, and secondary glaucoma. 29 In another study, researchers investigated structural and functional correlations and found better results for neural tissue-based indexes compared with LC-derived parameters. 30 In contrast to the results of the existing studies, BMO-MRW had the lowest diagnostic performance among all geometric parameters we evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers have been investigating new metrics based both on prelaminar neural tissue (PLNT) and laminar analyses [26][27][28]. The higher value of prelaminar neuronal tissue thickness (PLNTT) in early glaucoma diagnosis is evaluated and compared to conventional cpRNFL by Lopes et al [15] in large study, recently. To our knowledge, this is the first study that investigates the correlation between cpRNFLT 'that automatically segmented' and PLNTT 'that manually segmented' in both normal ONH and abnormal ONH.…”
Section: Discussionmentioning
confidence: 99%
“…None had used EDI-OCT parameters in neurological disease till now. Few authors investigate prelaminar neuronal tissue thickness (PLNTT) and relation to visual function and perimetry mean deviation [15]. But no one could investigate the correlation between PLNTT and cpRNFLT in normal and abnormal appearance ONH.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to current methods for measuring peripapillary retinal nerve fiber layer thickness, BMO-MRW measurement considers the varying path of axons across the location of measurement since it is made perpendicular to the axis of the neural tissue [ 70 , 71 ]. Chauhan et al reported that compared to RNFL thickness, BMO-MRW produced better diagnostic results for glaucoma with current confocal scanning laser tomography (CSLT) or SD-OCT based ONH and RNFLT parameters, excluding the superiornasal quadrant, which exhibited a greater sensitivity to RNFL thickness [ 71 , 72 , 73 ]. Jonas et al reported that RNFL thickness and BMO-MRW have comparable areas under the receiver operating characteristic curves (AUROCs) in distinguishing perimetric glaucoma eyes to normal eyes and both showed lower AUROCs in the pre-perimetric glaucoma group.…”
Section: Emerging Structural Diagnostic Biomarkersmentioning
confidence: 99%